2022
DOI: 10.14309/ctg.0000000000000481
|View full text |Cite
|
Sign up to set email alerts
|

Incidence Trends of Inflammatory Bowel Disease in a Southern European Country: A Mirror of the Western World?

Abstract: INTRODUCTION:Inflammatory bowel disease (IBD) affects people from all age categories worldwide. Although the incidence of the disease is stabilizing or decreasing in most Western world countries, its prevalence is still increasing because of the rise in life expectancy and better disease management. This work intends to identify the trends related to IBD incidence nationwide, analyzing regional, sex, and age distributions.METHODS:Data were provided by the Portuguese Shared Services of the Ministry of Health. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The latest epidemiological data for Belgium dates to the 1990s, documenting incidence rates of 4.1/100,000 for CD and 3.7/100,000 for UC patients. 25 , 26 In Portugal, Santiago et al 14 reported a high IBD incidence rate of 48.6/100,000 person-years. This study’s methodology, however, could not guarantee that all cases investigated had a confirmed diagnoses of IBD and thus may have included false-positive results.…”
Section: Incidence and Prevalence Of Ibdmentioning
confidence: 98%
See 4 more Smart Citations
“…The latest epidemiological data for Belgium dates to the 1990s, documenting incidence rates of 4.1/100,000 for CD and 3.7/100,000 for UC patients. 25 , 26 In Portugal, Santiago et al 14 reported a high IBD incidence rate of 48.6/100,000 person-years. This study’s methodology, however, could not guarantee that all cases investigated had a confirmed diagnoses of IBD and thus may have included false-positive results.…”
Section: Incidence and Prevalence Of Ibdmentioning
confidence: 98%
“…10,11 Although Southern European countries have often been considered as low prevalent areas for IBD, recent studies have proven this is no longer the case, as can be seen from recent studies from Spain, Italy and Portugal. [12][13][14][15][16][17] Western Europe is vast and disease rates vary not only between countries, but within each country itself. One of the largest UK studies to determine epidemiology rates in IBD explored health records from more than 38.3 million people between 2000 and 2020 and found a population incidence rate of 36 new cases per 100,000 person-years, with greater rates in Scotland and Northern Ireland compared to England and Wales.…”
Section: Incidence and Prevalence Of Ibdmentioning
confidence: 99%
See 3 more Smart Citations